Money and credit: twenty years of debate in Italy (1970-1990) - NARDOZZI, G. (PSL Quarterly Review, 2013)
This survey discusses the contributions of Italian economists to the analysis of questions relating to money credit and the financial system. The underlying reasons for the existence of money and the motivations for financial relations are first explored. Amongst the many important areas surveyed are those concerned with structural aspects of the financial system in Italy that are important to stability and efficiency. JEL Codes: E51, G10